Sistem Pendukung Keputusan Pemilihan Sepeda Motor Bekas dengan Metode AHP dan SAW (Studi Kasus: Sahabat Motor) - Nur Alam Arifin (Universitas Indraprasta PGRI Jakarta, 2020)
Buyers of used motorbikes in determining their choices, of course, are based on several criteria that are used as benchmarks in selecting used motorbikes, including the year of manufacture, engine capacity, color, type and price. These criteria are a consideration for buying a used motorbike, various considerations are made by the buyer in order to get a good and good used motorbike. The selection of used motorbikes to be purchased is not easy for prospective buyers who do not understand the ins and outs of used motorbikes. The difficulty in selecting used motorbikes requires a reference as a rationale for selecting used motorbikes. The decision support system offers a solution for referral in the selection of used motorbikes. The decision support system offered uses AHP and SAW in solving problems. Problems can be solved by using a ranking system based on global weights. Buyers of used motorbikes can choose used motorbikes based on referrals or recommendations from a decision support system run by experts. This system can help prospective buyers by providing alternative results for the choice of used motorbikes obtained from AHP and SAW calculations. Based on the calculation of the assessment criteria factors proposed to the system, the determination of used motorbikes is obtained through the calculation of priority weight values for the alternative selection of used motorbikes to be purchased. With the Decision Support System to choose a used motorbike using the AHP and SAW method, it is hoped that it can help prospective buyers in selecting used motorbikes and can produce optimal results that meet a high sense of satisfaction for prospective used motorcycle buyers.